2020
DOI: 10.1111/joa.13196
|View full text |Cite
|
Sign up to set email alerts
|

Geometric description for the anatomy of the mitral valve: A review

Abstract: The mitral valve is a complex anatomical structure whose physiological functioning relies on the biomechanical properties and structural integrity of its components.Their compromise can lead to mitral valve dysfunction, associated with morbidity and mortality. Therefore, a review on the morphometry of the mitral valve is crucial, more specifically on the importance of valve dimensions and shape for its function.This review initially provides a brief background on the anatomy and physiology of the mitral valve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…That being the case, an in vitro study enables individual variables to be reliably identified and manipulated which aid in objectively determining how altering a given parameter affects functionality; in our study, the data have provided evidence that strut chordae can play a role in preventing mitral regurgitation under conditions of annular dilation. The findings from this study suggest that there may be merit in further evaluating how dilation of specific segments of the annulus may link to the role of chordae in mitral valve competence; such a study would benefit from the geometry description for the mitral valve 1 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…That being the case, an in vitro study enables individual variables to be reliably identified and manipulated which aid in objectively determining how altering a given parameter affects functionality; in our study, the data have provided evidence that strut chordae can play a role in preventing mitral regurgitation under conditions of annular dilation. The findings from this study suggest that there may be merit in further evaluating how dilation of specific segments of the annulus may link to the role of chordae in mitral valve competence; such a study would benefit from the geometry description for the mitral valve 1 .…”
Section: Discussionmentioning
confidence: 97%
“…The mitral valve is composed of the anterior and posterior leaflets and chordae tendineae which connect these leaflets to papillary muscles and in turn the left ventricle. 1 During systole, the leaflets have to cover an orifice, the circumference of which is outlined by a ring of tissue known as the mitral annulus. Closure of the mitral valve leaflets during systole prevents mitral regurgitation, enabling blood to flow out of the aortic valve and through to the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were maintained hydrated throughout testing using Ringer's solution. 7,38,45 Tangent moduli (E) were calculated according to equations (1) and (2). Tangent moduli were calculated for both an initial high-extension phase and a subsequent low-extension phase for each chord.…”
Section: Materials Testingmentioning
confidence: 99%
“…Chordae tendineae connect papillary muscles, attached to the left ventricle, to the anterior and posterior leaflets of the mitral valve. 1,2 There are four types of chordae, characterised by their insertion points and corresponding geometry. 1,[3][4][5][6] Marginal chordae, which insert into the free edge of the leaflet, are often thinner and less extensible than other chordae.…”
Section: Introductionmentioning
confidence: 99%
“…The mitral valve consists of anterior and posterior leaflets connected to papillary muscles by chordae tendineae. 1 Chordae restrict the motion of the leaflets to prevent the prolapse of leaflets into the left atrium during systole. 2 Thus, the mitral valve's function is to prevent blood backflow during systole (into the left atrium), while allowing unrestricted unidirectional flow during diastole; this relies on mobility, elasticity and structural integrity of the valve's leaflets.…”
Section: Introductionmentioning
confidence: 99%